Decision support system for new student selection at railako vocational technical school using the TOPSIS method - Emeliana Lopes; Jaime Da Costa Lobo Soares (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2027)
The student admission selection process is a crucial stage in ensuring the quality of education, yet it is often conducted manually, leading to inefficiency and subjectivity. This study aims to develop a Decision Support System (DSS) for new student selection at Railako Vocational Technical School using the TOPSIS method. Data were collected through observation, interviews, and literature study, while system development employed the SDLC Waterfall model with PHP and MySQL implementation. The system evaluates candidates based on multiple criteria, including academic test scores, interview results, distance, and age. The results show that the TOPSIS method successfully ranks candidates objectively, with preference values of 0.625 (A2), 0.509 (A1), and 0.034 (A3), where A2 is identified as the best alternative. The system improves selection efficiency and reduces subjectivity compared to manual methods. This study contributes by integrating TOPSIS into a web-based system and demonstrating its effectiveness in real-case student selection scenarios.